Approaching the end: eschatological reflections on church, politics, and life - Hauerwas, Stanley (William B. Eerdmans Publishing Company, 2013)
In this book Stanley Hauerwas explores the significance of eschatological reflection for helping the church negotiate the contemporary world. In Part One, "Theological Matters," Hauerwas directly addresses his understanding of the eschatological character of the Christian faith. In Part Two, "Church and Politics," he deals with the political reality of the church in light of the end, addressing such issues as the divided character of the church, the imperative of Christian unity, and the necessary practice of sacrifice. End, for Hauerwas, has a double meaning -- both chronological end and end in the sense of "aim" or "goal." In Part Three, "Life and Death," Hauerwas moves from theology and the church as a whole to focusing on how individual Christians should live in light of eschatology. What does an eschatological approach to life tell us about how to understand suffering, how to form habits of virtue, and how to die? -- Publisher